2022
DOI: 10.7554/elife.76702
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous neuronal oscillations in the human insula are hierarchically organized traveling waves

Abstract: The insula plays a fundamental role in a wide range of adaptive human behaviors, but its electrophysiological dynamics are poorly understood. Here we used human intracranial electroencephalographic recordings to investigate the electrophysiological properties and hierarchical organization of spontaneous neuronal oscillations within the insula. We analyzed the neuronal oscillations of the insula directly and found that rhythms in the theta and beta frequency oscillations are widespread and spontaneously present… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(47 citation statements)
references
References 103 publications
(188 reference statements)
6
38
0
Order By: Relevance
“…Another study reported activity in frontal electrodes during the emotional processing of IAPS pictures [ 83 , 84 ]. The conscious perception of visceral activity is generally reported in the right hemispheric part of the Insula [ 85 ] that contributes in the experience of emotions in the beta band [ 86 ]. Marshall et al [ 84 ] reported activity in frontal, frontocentral and frontotemporal electrodes in top-down anticipation of the heartbeat signal with increased sensory perception in the context of emotionally negative and neutral faces.…”
Section: Discussionmentioning
confidence: 99%
“…Another study reported activity in frontal electrodes during the emotional processing of IAPS pictures [ 83 , 84 ]. The conscious perception of visceral activity is generally reported in the right hemispheric part of the Insula [ 85 ] that contributes in the experience of emotions in the beta band [ 86 ]. Marshall et al [ 84 ] reported activity in frontal, frontocentral and frontotemporal electrodes in top-down anticipation of the heartbeat signal with increased sensory perception in the context of emotionally negative and neutral faces.…”
Section: Discussionmentioning
confidence: 99%
“…Our method overcomes these challenges by customizing the analysis pipeline according to the iEEG recordings from each individual patient (15,43). This approach consists of two primary steps: (i) The first step consists of identification of spatially contiguous clusters of electrodes with narrowband oscillations at similar frequencies.…”
Section: Approach To Measure Traveling Waves Of Neuronal Oscillationsmentioning
confidence: 99%
“…Therefore, our first step in identifying these patterns is to detect oscillations that appear at a single frequency at multiple nearby electrodes. To detect such patterns, we first identify spatially contiguous clusters of electrodes with oscillations at the same or similar frequencies (15,43). Critically, we perform this procedure in an adaptive fashion that is well suited for human iEEG data by accommodating differences in electrode positions and oscillation frequencies across individuals.…”
Section: Identification Of Oscillations and Clustering Algorithmmentioning
confidence: 99%
See 2 more Smart Citations